De Novo Design of an Androgen Receptor DNA Binding Domain‐Targeted peptide PROTAC for Prostate Cancer Therapy. Issue 28 (15th August 2022) - Ma, Bohan; Fan, Yizeng; Zhang, Dize; Wei, Yi; Jian, Yanlin; Liu, Donghua; Wang, Zixi; Gao, Yang; Ma, Jian; Chen, Yule; Xu, Shan; Li, Lei
Abstract: Androgen receptor splice variant‐7 (AR‐V7), one of the major driving factors, is the most attractive drug target in castration‐resistant prostate cancer (CRPC). Currently, no available drugs efficiently target AR‐V7 in clinical practice. The DNA binding domain (DBD) is indispensable for the transcriptional activity of AR full length and AR splice variants, including AR‐V7. Based on the homodimerization structure of the AR DBD, a novel peptide‐based proteolysis‐targeting chimera (PROTAC) drug is designed to induce AR and AR‐V7 degradation in a DBD and MDM2‐dependent manner, without showing any activity on other hormone receptors. To overcome the short half‐life and poor cell penetrability of peptide PROTAC drugs, an ultrasmall gold (Au)‐peptide complex platform to deliver the AR DBD PROTAC in vivo is developed. The obtained Au‐AR pep‐PROTAC effectively degrades AR and AR‐V7 in prostate cancer cell lines, particularly in CWR22Rv1 cells with DC50 values 48.8 and 79.2 nM, respectively. Au‐AR pep‐PROTAC results in suppression of AR levels and induces tumor regression in both enzalutamide sensitive and resistant prostate cancer animal models. Further optimization of the Au‐AR pep‐PROTAC can ultimately lead to a new therapy for AR‐V7‐positive CRPC. Abstract : A novel peptide PROTAC targeting androgen receptor DNA binding domain via AI‐Rosetta assisted design for castration‐resistant prostate cancer therapy is presented.